The Role of Buddhist Preachers in Community Guidance Through Javanese Culture in Batu City - Suwito Suwito; Endang Suswati; Tri Cicik Wijayanti (CV. Ulil Albab Corp, 2026)
This study examines the role of Buddhist religious extension workers in fostering Buddhist communities in Batu through a Javanese cultural approach. It aims to analyze how the integration of local cultural values strengthens religious guidance amid challenges such as declining community participation and limited supporting resources. This study employed a descriptive qualitative method, with data collected through observation, in-depth interviews, and documentation at selected temples. The data were analyzed using triangulation techniques and SWOT analysis to identify the strengths, weaknesses, opportunities, and challenges in the community development process. The findings reveal that integrating Javanese cultural values with Buddhist teachings (Dhamma) strengthens social cohesion, enhances emotional connectedness between extension workers and community members, and reinforces a more adaptive cultural–religious identity. These findings suggest that a culture-based approach not only improves the effectiveness of religious extension services but also strengthens the spiritual resilience and sustainability of Buddhist communities amid ongoing social change.